Brand managers’ interfaces in different consumer goods industries - Panigyrakis, George G.; Veloutsou, Cleopatra A. (My University, 1999)
Focuses on how brand managers in fast-moving consumer goods industries view their contacts with the various interfaces, allocate their working time and perceive the significance and quality of these contacts. Based on the product management literature, several hypotheses are proposed and empirically examined using data collected from a sample of 161 product managers, working for 48 companies in five different sectors in Greece. The results show that brand managers working in various sectors differ in the perception of their contacts with the various interfaces. © 1999, MCB UP Limited
Keywords: Brands; Greece; Interface management; Interfaces; Internal communications; Product management